RESOLUSI KONFLIK BERLATAR AGAMA: STUDI KASUS AHMADIYAH DI KUDUS - Moh. Rosyid (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
The purpose of this research are knowing the life of the Ahmadi community member in the city of Kudus, Central Java which can live together in peace with moslem people there; exploring conflict resolution model done by the Ahmadi community member in the city of Kudus, Central Java. The main source of the data of this research are observation and indepth interviews. The research methode used in this study was qualitative research methods. The results show that the Ahmadi community member in the city of Kudus did the conflict resolution so well in encountering conflict. These are: distributing flyers to residents of Colo, Kudus in 2006. Words written on flyers is “the same God, the same Prophet; in their mosque written “Laailahaillallah Muhammdurrasulullahilla; they embedded in social activities with the resident of non - Ahmadis in Colo; they are proactive and adhere to the the regulation and social norms which prevailing in their communites and living together with the all the Colo residents.